AN ANALYSIS ON THE STUDENTS’ TRANSLATION TECHNIQUES IN TRANSLATING A POEM - GINA SRI WAHYUNI (Journal of English Education Program (JEEP), 2015)
This paper was an analysis on the students’ translation techniques in translating poem entitled “You’ll live, But I’ll Not ...” by Anna Akhmatova. This study was a case study since it was carried out in a small case and single case. In this case, the entire students who joined translation subject consisting of 60 students at the fourth grade of English department of Galuh University and were selected by using purposive sampling technique to gain the sample. As a result, two students were chosen as sample to conduct the research. The writer used the students’ translation test to answer the first and the second research questions. In analyzing the data, the writer used the steps adapted from Fraenkel and Wallen (2007, p. 425-427). The results of analysis concluded that deletion, literal translation, adaptation, modulation, transposition, and addition were techniques used by the translators in translating poem “You’ll live, But I’ll Not ...” by Anna Akhmatova. Meanwhile, the results also revealed that ambiguity, grammar, linguistic translation, cultural translation, pragmatic translation, and text-specific translation were problems faced by the translators in translating poem entitled “You’ll live, But I’ll Not ...” by Anna Akhmatova.   Key words: translation, techniques, poem.